Budaya Organisasi: Dampaknya Pada Peningkatan Daya Saing Perusahaan - Wilson Bangun (Universitas Kristen Maranatha, 2008)
The organizational culture is one of indicators indicates to increase the corporate comparative advantage. The organization’s succes depends on the increasing of performance, in other side the failure of organization comes from the decreasing in performance. The purpose of this research is to explore the concept of the organizational culture and its role in achieving organizational success. The type of research used was library research. The organizational culture consist three levels, such as artifact, espoused values, and basic assumption. Organizational culture has to differentiate between strong and weak culture. Strong cultures have a greater impact on employee behaviors and are more directly related to reduce turnover.